Dejima; VOC dan "rangaku" - Wibawarta, Bambang (Wacana, Journal of the Humanities of Indonesia, 2008)
Japan and the Netherlands have maintained a special relationship for about 300 years since the adoption of the National Seclusion policy, the so-called sakoku by the Tokugawa shogunate (1603-1867). The Dutch began trading with Japan and engaging with Japanese society in 1600, when a Dutch ship, De Liefde, arrived in Kyushu. The Tokugawa government measures regarding foreign policy included regulations on foreign access to Japan and a prohibition on Japanese going abroad. Between the middle of the seventeenth to the early nineteenth century, Japan was characterized by a stable political pattern in which representatives of the VOC (Dutch East India Company), were the only Europeans with a right to trade in Japan. In the course of this period, the Japanese evaluation of the Dutch changed from regarding them as commercial agents to seeing them as importers of European knowledge. This paper is especially concerned with the influence of the so-called 'Dutch Studies' (rangaku) on the early modernization of Japan, especially with regard to medicine and the natural sciences. This research examines the development of rangaku and the trading between Japan and VOC at Dejima.